REKONSTRUKSI PENDIDIKAN ISLAM BERBASIS PEMBENTUKAN KARAKTER: DARI KONSEP MENUJU INTERNALISASI NILAI-NILAI AL-QURAN - Asri Karolina (Jurnal Penelitian, 2017)
REKONSTRUKSI PENDIDIKAN ISLAM BERBASIS PEMBENTUKAN KARAKTER: DARI KONSEP MENUJU INTERNALISASI NILAI-NILAI AL-QURANAbstractThis paper examined the reconstruction of Islamic education which is still facing various problems. Educational outcomes also still do not meet the expected of Islamic education goals. Beside of that, the classroom learning also has not been able to produce the young generation which has personalities that reflect a value of Muslim character. The process of Islamic education now is still focused and concentrated on the achievements of cognitively only without caring out the affective aspect which has a strong provision to socialize with the community. The implementation of Islamic education itself is still in the level of concept, not on the internalization of the Qur'an values which is the true basis of its. Furthermore, when we talking about the formation of morals related to the educational goals, especially Islamic education. As for the increasingly worrisome problem is the rise of cases of moral decadence.  Some cases about the degradation of the human beings dignity which has flourished in society even in the world of education were undertaken by learners, such as the destruction of Islamic values, the outbreak of bullying cases, and the rising of immoral cases. This phenomenon seems to re-question of Islamic education role in the shaping of the learner's character. Therefore, it is necessary to reconstruct the Islamic education based on character formation with the concept of internalization of Al-Quran values. The results of this paper explained that there were 3 things that can be done in reconstructing Islamic education-based on the character formation with the concept of internalization of Al-Quran values were: first, educators must make personal recognition with learners. Second, all parties involved in educational institutions should present themselves as role models for learners. Third, in applying the education based on Al-Quran there are 4 stages that have to imply first that are: the learning experience, reflection, action, and evaluation. Keywords: Islamic Education, Character Building,Quranic Values